Бунін і Гоголь: український чинник, або Між Орловщиною і Провансом - Барабаш, Ю. (Слово і Час, 2021)
Розглядається як історико-літературний факт і психологічний феномен-загадка розрив між двома оцінками І. Буніним особистості та
творчості М. Гоголя — від юнацького захоплення до «ненависті» у
зрілі літа. Ключовим є питання про місце й роль «українського чинника» в біографії та творчості Буніна, про його інтерес та емпатію
до України, її людей, природи, історії, культури, до Т. Шевченка. Саме
через поезію Шевченка й ранні повісті Гоголя Україна відкрилася молодому Буніну. Щодо його пізнішого негативного ставлення до Гоголя,
то тут визначальними постають відмінності особистісного плану,
несхожість поетик, пов’язана зі зміною історико-літературної парадигми, зокрема в напрямку модернізму. The gap as long as several decades between I. Bunin’s different opinions of Gogol’s personality and writings — from youthful admiration and feeling of emotional and spiritual proximity to the confession of ‘hatred’ in a diary note of emigrant times — has been considered both as historical-literary fact and psychological mysterious phenomenon. The key problem determining the angle of an analytical approach to the topic is the role and significance of the ‘Ukrainian factor’ in Bunin’s biography and literary art, his interest and affection towards Ukraine, its people, nature, history, traditions, and culture, which was testified by the writer’s confessions and became the subject of research in the Ukrainian scholarly discourse and journalism (E. Malaniuk). In that light, the stories by Bunin based on his traveling around Ukraine, the parts of the novel “Аrseniev’s life”, memoir and epistolary materials have been analyzed in the paper. Special attention has been paid to Bunin’s tender attitude towards T. Shevchenko, his creative works and his personality. It was Shevchenko’s poetry as well as “A Terrible Revenge” and “The Old-World Landowners” by Gogol that revealed Ukraine to young Bunin, entering his conscience and creative imagination. As to the later Bunin’s negative attitude towards Gogol, the decisive factors were dissimilarity of both writers’ personal and psychological features and difference of their creative methods and poetics, connected with the change of historical and literary paradigm. In particular, Gogol was the forerunner to modernism from which Bunin stayed away.